Tatalaksana Teknologi Informasi Metode COBIT - Ardi Hamzah (Universitas Kristen Maranatha, 2004)
COBIT method necessary implementation in enterprise management in order that using Information Technology (IT) appropriate with need of enterprise and performance output that eflicient and effective along with preventive or minimize of risk on using IT. Using and management IT also consider of integration, where hardware, software, and brainware constitute integration.Keywords: cobit method, information technology, hardware. software, brainware